1997
DOI: 10.1111/j.1349-7006.1997.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fas Antigen and Its Mediation of Apoptosis in Human Gastric Cancer Cell Lines

Abstract: Fas, a member of the tumor necrosis factor receptor/nerve growth factor receptor family, induces apoptosis by crosslinking with Fas ligand or anti‐Fas antibody in a variety of cultured cells. We examined the expression of Fas antigen and its mediation of apoptosis in six human gastric carcinoma cell lines. Flow cytometric analysis and western blotting revealed relatively high expression of Fas antigen in MKN‐74 (wild‐type p53 gene) and MKN‐45 (wild‐type), followed by MKN‐1 (mutated), MKN‐7 (mutated) and KATO‐I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Western blot analysis showed that only one antibody for Fas or FasL detected single bands of about 45 and 37 kDa, corresponding to Fas and FasL, respectively. Moreover, Fas and FasL expressions were variable among the human gastric carcinoma cell lines we tested, and minimal expression of Fas was noted in MKN-28, which has been shown to be resistant to antiFas antibody-induced apoptosis [21]. Thus, it is unequivocal that Fas and FasL are expressed in human gastric tumors, although their actual roles and biological significance are largely unknown.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Western blot analysis showed that only one antibody for Fas or FasL detected single bands of about 45 and 37 kDa, corresponding to Fas and FasL, respectively. Moreover, Fas and FasL expressions were variable among the human gastric carcinoma cell lines we tested, and minimal expression of Fas was noted in MKN-28, which has been shown to be resistant to antiFas antibody-induced apoptosis [21]. Thus, it is unequivocal that Fas and FasL are expressed in human gastric tumors, although their actual roles and biological significance are largely unknown.…”
Section: Discussionmentioning
confidence: 93%
“…SDS-PAGE and Western blot analysis were performed as described previously [21]. To evaluate the specificity of antibodies against human Fas and FasL, one polyclonal and two monoclonal anti-Fas antibodies and one polyclonal and three monoclonal anti-FasL antibodies were used.…”
Section: Sodium Dodecylsulfate-polyacrylamide Gel Electrophoresis (Sdmentioning
confidence: 99%
“…Fas is a 45 kDa cell surface proteins that mediates apoptosis in a variety of cell types (Trauth et al, 1989;Yonehara et al, 1989;Itoh et al, 1991;Oehm et al, 1992;Ogasawara et al, 1993). Fas is expressed by several tumor, including gastric cancers (Hayashi et al, 1997). Western blot analysis demonstrated intense expression of Fas antigen in MKN-45 gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of the Fas receptor is detected both in cell lines derived from human gastric cancers (12) and in gastric carcinoma tissue specimens (36). Bennett et al (2) detected enhanced Fas ligand expression in 30 gastric carcinomas and suggested that expression of Fas ligand allows gastric cancers to escape immune surveillance by inducing cell death in infiltrating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%